KONSEP MIMPI DALAM PEMIKIRAN SIGMUND FREUD: PERSPEKTIF FILSAFAT MANUSIA - UNINGOWATI, DWI WAHYUNI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The title of this research is the concept of dreams within the thought of Sigmund Freud: a human philosophy perspective. Freud with the concept of dreams are going to be delved together in its relationship with human personality which is one of the teaching aspects of human philosophy. The purpose of this research is to describe the concept of dreams according to Sigmund Freud, to explain the ideas of Sigmund Freud about human personality, and to find their relevances toward social condition in Indonesia. This research was conducted using the method of literature review in characterization factual historical, and contained the concept of dreams according to Freud as the material object, and the human philosophy especially human personality as formal object. The method implemented was hermeneutics included two methodical elements which were description, vertehejn, and interpretation of the ideas of Freud and heuristics in order to gain a new paradigm extracted from those ideas which were expected could play a useful role to social life in Indonesia. The results of the research were, first, the concept of dreams according to Sigmund Freud was a fulfillment of expectations, a realization of fear, an expression, a warning, and a consideration of problems. Second, the human personality contained three dynamically interacted elements that were identity, ego, and superego. Third, their relevance toward social condition in Indonesia was appeared in the phenomenon of sexual abuse that had taken place in number of times.